Age- and gender-specific differences in the prognostic value of CT coronary angiography. Issue 3 (13th September 2011) - Yiu, Kai Hang; de Graaf, Fleur R; Schuijf, Joanne D; van Werkhoven, Jacob M; Marsan, Nina Ajmone; Veltman, Caroline E; de Roos, Albert; Pazhenkottil, Aju; Kroft, Lucia J; Boersma, Eric; Herzog, Bernhard; Leung, Melissa; et al.
Abstract : Objective: To evaluate the potential age- and gender-specific differences in the incidence and prognostic value of coronary artery disease (CAD) in patients undergoing CT coronary angiography (CTA). Design and patients: In this multicentre prospective registry study, 2432 patients (mean age 57±12, 56% male) underwent CTA for suspected CAD. Patients were stratified into four groups according to age <60 or ≥60 years and, male or female gender. Main outcome measures: A composite end point of cardiac death and non-fatal myocardial infarction. Results: CTA results were normal in 991 (41%) patients, showed non-significant CAD in 761 (31%) patients and significant CAD in the remaining 680 (28%) patients. During follow-up (median 819 days, 25–75th centile 482–1142) a cardiovascular event occurred in 59 (2.4%) patients. The annualised event rate was 1.1% in the total population (men=1.3% and women=0.9%). In patients aged <60 years, the annualised event rate of male and female patients was 0.6% and 0.5%, respectively. Among patients aged ≥60 years the annualised event rate was 1.9% in male and 1.1% in female patients. Observations on CTA predicted events in male patients, both age <60 and ≥60 years and in female patients age ≥60 years (log-rank test in all groups, p<0.01). However, CTA provided limited prognostic value in female patients aged <60 years (log-rank test, p=0.45). Conclusions: After age and gender stratification, CTA findings were shown to be of limited predictive value in female patients aged <60 years as compared with male patients at any age and female patients aged ≥60 years.